Three-segment steel brace for seismic design of concentrically braced frames. (October 2017) - Seker, Onur; Akbas, Bulent; Seker, Pinar Toru; Faytarouni, Mahmoud; Shen, Jay; Mahamid, Mustafa
Abstract: A three-segment steel brace has been developed and investigated by means of numerical and experimental studies. The objective of the development was to develop a brace member that exhibits stable and symmetrical cyclic response under cyclic loading. The concept was conceived by extending a conventional elastic buckling of a column with variable sections to include post-buckling deformation. The concept was first examined using FEM-based simulations, and tested experimentally with an ensemble of small-scale brace specimens under cyclic loads. Seismic response of CBFs with conventional buckling braces and the three-segment braces were compared and results are discussed in terms of drift, brace and beam ductility demands. The results indicate that the tested three-segment braces specimens were capable of exhibiting stable and symmetrical hysteretic response, as well as dissipating a greater amount of energy compared to conventional buckling braces. Further, the dynamic analyses results point out that substituting the conventional buckling braces with the three-segment braces substantially mitigates the seismic demand on the braced frames. Highlights: Post-buckling behavior substantially reduces the overall energy dissipation capacity of CBF. Three-segment brace shows stable hysteresis, dissipating more energy than conventional buckling brace does. Substituting three-segment braces for the conventional buckling braces mitigates the seismic demand on the braced frames.